Errors in Using Past Tense Form in Writing Essays among Kurdish University Learners - Ali, Karker Ali; Mostafa, Nor Azmi (AJELP: Asian Journal of English Language and Pedagogy, 2013)
The study was conducted to identify the common errors in the use of past tense form made by Kurdish learners of English language when writing essays and to investigate the factors that influenced these errors and how the Kurdish first language affect their process of learning English language. The participants for this study were from the English Department, Faculty of Humanities, University of Duhok. A total of 29 students participated in this study. All the errors were identified and classified into various categorizations. The results of the study showed seven most common errors in the use of past tense form committed by the participants which were simple past, past progressive, past perfect, past passive, future in the past, irregular verbs and regular verbs. The findings also showed that the errors committed were influenced by the use of the participants ‟first language (mother tongue) and intralingual factors. On the basis of these findings, the researcher discussed some pedagogical implications and provided suggestions for teachers and future researchers.